DESIGN OF A PROTOTYPE OF WATER QUALITY PHYSICS MEASURING EQUIPMENT BASED ON MICROCONTROLLER - Riky Arisandi; Ari Purno Wahyu Wibowo (Jurusan Informatika Universitas Jenderal Achmad Yani, 2022)
Normal water temperature is the water temperature that allows living things to metabolize and reproduce. Temperature is a very important physical factor in water. The temperature and the substances/elements contained therein will determine the density, density and saturation of water. The water temperature will be different from one point to another or different based on a certain depth. The difference is caused by differences in geographical latitude and the position of a body of water with respect to the sun, causing the reception of solar radiation in each region to be different. Given the importance of clean water sources, it is necessary to have a monitoring system and read water quality so that it can be used and utilized for consumption and irrigation, so that in this study a micronotroller-based water monitoring system was created which was installed in water sources and watersheds, from the system it could be directly a water quality analysis process is carried out based on the pH and other elements that can be directly used as a measurement parameter and can be presented in real time and accurately.